2021
DOI: 10.33963/kp.a2021.0130
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary embolism response team: A multidisciplinary approach to pulmonary embolism treatment. Polish PERT Initiative Report

Abstract: Background: A pulmonary embolism response team (PERT) is a multidisciplinary team established to improve clinical care for patients with pulmonary embolism (PE). However, data regarding detailed institutional experience and clinical outcomes from such teams are sparse. Aims:We aim to assess the frequency of activations, patients' characteristics, PE severity, applied treatments, and outcomes of PE patients treated by Polish PERTs. Methods:The survey registry was conducted between June 2018 and July 2020. All c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…Araszkiewicz et al [7] report the use of systemic anticoagulation alone in 80% of PERT activations, higher rates than prior retrospective reports [5,11], but consistent with the notion that most acute PE patients cared for by PERT teams do well with anticoagulation alone. While the implementation of PERT teams is associated with an increased use of advanced PE therapies, these invasive and riskier strategies should not be used liberally, and are best utilized in experienced operators' hands, depending on the local resources and expertise, and in the context of an individualized treatment plan.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…Araszkiewicz et al [7] report the use of systemic anticoagulation alone in 80% of PERT activations, higher rates than prior retrospective reports [5,11], but consistent with the notion that most acute PE patients cared for by PERT teams do well with anticoagulation alone. While the implementation of PERT teams is associated with an increased use of advanced PE therapies, these invasive and riskier strategies should not be used liberally, and are best utilized in experienced operators' hands, depending on the local resources and expertise, and in the context of an individualized treatment plan.…”
supporting
confidence: 57%
“…In this context, the study by Araszkiewicz et al [7] in the current issue of Kardiologia Polska (Kardiol Pol, Polish Heart Journal) represents a welcomed addition to the PERT literature. The authors present the polish PERT initiative, by describing the first national, multicenter analysis of patients cared for by four PERTs between 2018 and 2020.…”
mentioning
confidence: 95%
“…The results of the present analysis indicate that the implementation of PERTs is a concept still predominantly implemented in the US. Even though the concept of PERT teams has been endorsed by the 2019 ESC Guidelines, only one study originated in Europe, notably in Poland, and reported on the composition and function of PERTs [ 15 ]. The rationale behind the implementation and structure of PERTs is based on the “heart team” concept, which facilitates patient management with a consensus opinion of different specialists and leads to improved organisation of teams and utilisation of resources [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The retrospective nature of the study did not allow the exclusion of hidden confounders such as preexisting cardiac or pulmonary diseases or other comorbidities that could affect the findings and the outcomes. A PE response team (PERT) is a multidisciplinary team established to improve the clinical care for patients with PE [ 21 , 22 ]. Although Rapid Response Teams (RRT) are always available in our institution, however, specialized teams that deal with PE such as the PERT are not.…”
Section: Discussionmentioning
confidence: 99%